005.2 Diagnostic and clinical implications of genotypic fluoroquinolone susceptibility detection for neisseria gonorrhoeae. (13th September 2015) - Pond, MJ; Hall, C; Cole, M; Laing, KG; Miari, V; Jagatia, H; Harding-Esch, E; Monahan, I; Planche, T; Hinds, J; Ison, C; Chisholm, S; et al.
Abstract : Introduction: Antibiotic resistance poses major challenges to empirical treatment of Neisseria gonorrhoeae (NG), potentially addressable if antimicrobial susceptibility point of care (POC) tests were available. The performance of a POC compatible real-time PCR assay (GCSNP), enabling detection of fluoroquinolone susceptible NG directly on clinical samples from multiple anatomical sites and on diverse circulating strains, was evaluated. Methods: Residual routine nucleic acid amplification test samples, derived from patients who were also culture positive for NG at the same clinical attendance were GCSNP tested. Assay performance was further verified using a phenotypically characterised fluoroquinolone resistant and susceptible strain panel which was sequence-typed using NG-MAST (NG Multi Antigen Sequence Typing). Results: 290 residual samples derived from 222 clinical episodes (56 female; 166 male) were tested by GCSNP, yielding result in 90% (n = 262/290), with assay failure more likely in non-genital compared to genital samples (16.4% vs. 5.2%, p = 0.002). 29.7% (n = 66/222) of NG cases were attributable to fluoroquinolone resistant strains in at least one anatomical site. GCSNP predictive values for fluoroquinolone susceptibility were 100% (95% CI: 95.9–100%) and 100% (82.8–100%), respectively for urogenital (n = 173) and rectal samples (n = 37). In four episodes of multi-anatomical-site infection (3 male, 1 female) different antimicrobial susceptibility profiles were observed across sample sites but all were correctly genotyped using GCSNP. GCSNP panel testing correctly identified all of 92 phenotypically susceptible (n = 52) and resistant (n = 40) strains. A total of 66 diverse NG-MAST sequence types were observed in the panel. Conclusion: GCSNP testing enables accurate genotypic detection of fluoroquinolone susceptible NG from clinical samples, from multiple anatomical sites and across diverse circulating gonococcal strains, enabling use of tailored anti-gonococcal therapy following NAAT positivity. If multi-site infection is suspected, genotypic testing on all anatomical sites is necessary in order to account for the presence of infections with mixed susceptibility. Disclosure of interest statement: This study was funded under the UKCRC Translational Infection Research (TIR) Initiative supported by the Medical Research Council (Grant Number G0901608) with contributions to the Grant from the Biotechnology and Biological Sciences Research Council, the National Institute for Health Research on behalf of the Department of Health, the Chief Scientist Office of the Scottish Government Health Directorates and the Wellcome Trust.